In vivo horizontal oncogenesis by a human tumor in nude mice. - Goldenberg, D M (1982)
A human mucinous cystadenocarcinoma of the ovary was propagated in nude mice. After cryopreservation of the 3rd-passage xenograft for 4 years, subsequent in vivo transplants showed the emergence of two distinct populations, one resembling the original human adenocarcinoma and the other resembling a spindle-cell sarcoma. These two tumor cell populations were confirmed to be human and murine, respectively, by cytogenetic study, and the epithelial tumor cells were further shown to be of human origin by immunoperoxidase staining of blood group A antigen. Separation of the two tumor cell populations in vitro permitted the independent propagation of the human and murine tumor cells in vitro and in vivo. The murine sarcoma was also capable of growth in ordinary BALB/c mice. These results indicate that human cancer cells can induce malignancy in adjacent, putatively normal, cells of nude mice in vivo.